STUDI KELAYAKAN USAHA AGROINDUSTRI DODOL MARKISA DI KELURAHAN MALINO KECAMATAN TINGGIMONCONG KABUPATEN GOWA - Nur Salam Achmad; Husain Syam; Lahming Lahming (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to describe the profits of passion fruit dodol processing business in Village Malino Subdistrict Tinggimoncong Gowa Regency, and to know the economic feasibility of passion fruit dodol processing business in Village Malino Subdistrict Tingimoncong, Gowa Regency. This research is a qualitative and quantitative research using descriptive analysis method. Data collection techniques used in this study is by interview with business owners. The qualitative data is presented in the non-financial aspect, while the quantitative data uses the economic analysis of BCR (Net Present Value), IRR (Internal Rate of Retrun), BEP (Break Event Point) and PBP (Pay Back Period). The results showed that the number profits of passionfruit dodol in Village Malino Subdistrict Tinggimoncong Gowa Regency within one year of Rp. 165,199,813, BCR (Benefit Cost Ratio) 1.6> 0, NPV (Net Present Value) 248,347,965> 0, IRR (Internal Rate of Retrun) 21%, BEP (Break Event Point) with packaging selling price 200 gr Rp. 4.482, packaging 300 gr Rp. 6.673, PBP (Pay Back Period) 2.3 years. Overall agroindustry dodol passion fruit  in Village Malino Subdistrict Tinggimoncong Gowa Regencyis economically feasible